Analisis Strategi Activity Based Costing dalam Mitigasi Distorsi Biaya - Swandani Swandani; Hayyun Aini (SUSTAINABLE, 2026)
This study examines the strategic role of Activity Based Costing (ABC) in mitigating cost distortion at PT Biringkassi, a company characterized by complex production processes and high overhead cost intensity. A descriptive quantitative approach was applied, utilizing data obtained from interviews as well as supporting primary and secondary sources. The results indicate that the traditional costing system, which relies on a single allocation base, is unable to accurately reflect resource consumption, resulting in cost distortion in the form of undercosting for products with higher complexity levels. The application of the ABC method leads to an increase in the cost of goods manufactured (COGM) for all products, indicating that previous cost calculations were underestimated relative to actual conditions. These findings confirm that the ABC method not only improves cost accuracy but also supports more effective managerial decision-making, particularly in pricing strategies and product performance evaluation. Given the complexity and high overhead structure of the cement industry, the adoption of ABC is essential to enhance efficiency and competitiveness.